2013
DOI: 10.1002/art.38107
|View full text |Cite
|
Sign up to set email alerts
|

Rituximab‐Induced T Cell Depletion in Patients With Rheumatoid Arthritis: Association With Clinical Response

Abstract: Objective Rituximab, a monoclonal antibody specifically targeting CD20, induces B cell depletion and is effective in the treatment of rheumatoid arthritis (RA). This study was undertaken to evaluate whether routine monitoring of lymphocyte subpopulations, especially T cells, may be useful in patients receiving rituximab for RA. Methods We examined data on all RA patients receiving rituximab between July 2007 and November 2012 in our center. Peripheral blood CD3+, CD4+, CD8+, CD3−CD56+, and CD19+ lymphocyte cou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
93
0
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 142 publications
(103 citation statements)
references
References 27 publications
(36 reference statements)
7
93
0
3
Order By: Relevance
“…Pathogenic functions of B cells in MS, therefore, are more likely to include antigen presentation, cytokine/chemokine production and/or T-cell co-stimulation, all adding up to the T-cell-mediated responses. This is supported by the fact that reduced numbers of T cells were observed in the circulation after rituximab treatment [153] . With respect to cytokine production, B-cell-depleting therapies have increased awareness that B cells may produce pro-and anti-inflammatory cytokines.…”
supporting
confidence: 63%
“…Pathogenic functions of B cells in MS, therefore, are more likely to include antigen presentation, cytokine/chemokine production and/or T-cell co-stimulation, all adding up to the T-cell-mediated responses. This is supported by the fact that reduced numbers of T cells were observed in the circulation after rituximab treatment [153] . With respect to cytokine production, B-cell-depleting therapies have increased awareness that B cells may produce pro-and anti-inflammatory cytokines.…”
supporting
confidence: 63%
“…The incidence rates of HZ were higher in rituximab (3.9 per 100 patient-years) and abatacept (8.5 per 100 patient-years) period compared to cDMARDs period. Several studies have been reported that rituximab induces T cell depletion, mainly of CD4+ T cells in patient with RA [21,22]. Based on these results, decreased of CD4+ T cell counts after rituximab therapy would be made and consequently might affect to RA patients to be more vulnerable to HZ.…”
Section: Discussionmentioning
confidence: 86%
“…It is well established that rituximab depletes B cells by inducing antibody-dependent cellmediated cytotoxicity upon binding Fcy receptor on the surface of effector immune cells, inducing non-classical apoptosis of B cells by crosslinking of multiple CD20 molecules, and mediating complementdependent cytotoxicity [22,23]. Rituximab ability to decrease CD4+ T cells in rheumatoid arthritis has been associated with clinical response [26]. A possible mechanism of rituximab depletion of CD4+ T cells may be by inhibiting an activation pathway of CD4+ cells initiated by the antigen presenting function of B cells or by inhibiting stimulation of CD4+ cell proliferation after priming by dendritic cells [27].…”
Section: Discussionmentioning
confidence: 99%